The Optimal L2 Error Estimate of Stabilized Finite Volume Method for the Stationary Navier-Stokes Problem. (11th November 2012) - He, Guoliang; Su, Jian; Dai, Wenqiang
Abstract : A finite volume method based on stabilized finite element for the two-dimensional stationary Navier-Stokes equations is analyzed. For the P 1 – P 0 element, we obtain the optimal L 2 error estimates of the finite volume solution u h and p h . We also provide some numerical examples to confirm the efficiency of the FVM. Furthermore, the effect of initial value for iterative method is analyzed carefully.